Analisis Yuridis Terhadap Pekerja Yang Terdampak Pengalihan Perusahaan Dalam Prespektif Perlindungan Hukum dan Keadilan - Ismarilda, Ismarilda; Setiawan, Puguh Aji Hari; Rae, Nyoman Tio (Jurnal Inovasi Global, 2025)
This research examines the issue of legal protection for workers affected by corporate transfers through mergers, acquisitions, or consolidations. In today's business environment, such corporate actions are common strategies to improve efficiency and expand market share, but often bring significant impacts on workers' status and rights. This study uses a normative juridical method with statutory and conceptual approaches, analyzing Law No. 13 of 2003 on Manpower, Law No. 40 of 2007 on Limited Liability Companies, and Government Regulation No. 35 of 2021. The research findings reveal that current regulations permit layoffs under corporate restructuring scenarios, but in practice are often misused without regard to justice principles and without adequate compensation guarantees. The overlap between labor law and corporate law creates ambiguity in implementation. The research emphasizes the importance of clear separation between legal provisions governing layoffs and those addressing corporate acquisitions, as well as strengthening regulations that ensure legal certainty, rights protection, and social justice for workers.